Length of hospital stay for elective electrophysiological procedures: a survey from the European Heart Rhythm Association - Boriani, Giuseppe; Imberti, Jacopo F.; Leyva, Francisco; Casado-Arroyo, Ruben; Chun, Julian; Braunschweig, Frieder; Zylla, Maura Magdalena; Duncker, David; Farkowski, Michał M; Pürerfellner, Helmut; Merino, José L. (Europace, 2023)
Abstract - - Aims - Electrophysiological (EP) operations that have traditionally involved long hospital lengths of stay (LOS) are now being undertaken as day case procedures. The coronavirus disease-19 pandemic served as an impetus for many centres to shorten LOS for EP procedures. This survey explores LOS for elective EP procedures in the modern era. - - - Methods and results - An online survey consisting of 27 multiple-choice questions was completed by 245 respondents from 35 countries. With respect to de novo cardiac implantable electronic device (CIED) implantations, day case procedures were reported for 79.5% of implantable loop recorders, 13.3% of pacemakers (PMs), 10.4% of implantable cardioverter defibrillators (ICDs), and 10.2% of cardiac resynchronization therapy (CRT) devices. With respect to CIED generator replacements, day case procedures were reported for 61.7% of PMs, 49.2% of ICDs, and 48.2% of CRT devices. With regard to ablations, day case procedures were reported for 5.7% of atrial fibrillation (AF) ablations, 10.7% of left-sided ablations, and 17.5% of right-sided ablations. A LOS ≥ 2 days for CIED implantation was reported for 47.7% of PM, 54.5% of ICDs, and 56.9% of CRT devices and for 54.5% of AF ablations, 42.2% of right-sided ablations, and 46.1% of left-sided ablations. Reimbursement (43-56%) and bed availability (20-47%) were reported to have no consistent impact on the organization of elective procedures. - - - Conclusion - There is a wide variation in the LOS for elective EP procedures. The LOS for some procedures appears disproportionate to their complexity. Neither reimbursement nor bed availability consistently influenced LOS.
Gesehen am 09.01.2024